Excess adiposity and survival in patients with colorectal cancer: a systematic review. Issue 5 (17th January 2014) - Parkin, Edward; O'Reilly, Derek A; Sherlock, David J; Manoharan, Prakash; Renehan, Andrew G
Summary Excess adiposity is an established risk factor for incident colorectal cancer (CRC) but whether this association extrapolates to poorer survival is unclear. We undertook a systematic review to examine relationships between measures of adiposity and survival in patients with CRC. For distinction, we included pre‐diagnosis exposure and CRC‐related mortality. We performed dose‐response meta‐analyses and assessed study quality using eight domains of bias. Six study categories were identified based on (i) timing of adiposity measurement relative to survival analysis time zero and (ii) clinical setting. Several types of adiposity measurements were reported; body mass index (BMI) was the commonest. For pre‐diagnosis cohorts, baseline BMI negatively impacted on CRC‐related mortality in men only (risk estimate per 5 kg m−2 = 1.19, 95% confidence intervals: 1.14–1.25). The other groups were pre‐diagnosis BMI but diagnosis as time zero; population‐based cohorts; treatment cohorts; observational analyses within adjuvant chemotherapy trials; patients with metastatic CRC – each had several biases (e.g. treatment selection, reverse causality) and sources of confounding (e.g. chemotherapy 'capping'). Overall, there was insufficient evidence for a strong link between adiposity and survival. These findings demonstrate an important principle: an established link between an exposure (here, adiposity) and increased cancer incidence does not necessarily extrapolate into an inferior post‐treatment outcome.